Pengaturan Negeri Dalam Peraturan Daerah Di Kabupatan Seram Bagian Barat - Samatuak, Obbie Yandri; Pietersz, Jemmy Jefry; Pattipawae, Dezonda Rosiana (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The conflict between the SBB Regional Regulation Number 11 of 2019 concerning Villages and the SBB Regional Regulation Number 13 of 2019 concerning the State. where it has been determined that all 92 customary lands in the West Seram Regency as villages in the SBB Regional Regulation Number 11 of 2019 while in the SBB Regional Regulation Number 13 of 2019 until now the countries that already exist as customary lands in Seram Regency have not been determined.Purposes of the Research: This writing aims to find out and analyze the legal consequences of State regulations in Regional Regulation Number 11 of 2019 concerning Villages and Regional Regulation Number 13 of 2019 concerning the State against the State in West Seram Regency.Methods of the Research: The research method used is normative juridical. which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: The results of the study show that the  determination of customary lands carried out by the SBB Regency Government in SBB Regional Regulation Number 11 of 2019 Article 3 can basically be said to be not in accordance with applicable procedures. This can be seen from the issuance of Regional Regulation SBB Number 13 of 2019 concerning the country in Article 4 paragraph 3 which states that "The determination of customary law community units is carried out through identification of customary law communities by observing: a). History of indigenous peoples; b). Customary territory; c). Customary law; d). Assets and/or customary objects; and e). Customary government institutions/systems. The substance in the SBB Regional Regulation Number 13 of 2019 Article 4 paragraph (3) is a valid requirement in the supporting Article of the legal consequences of the land regulated in the SBB Regional Regulation Number 13 of 2019 so that the determination of the 92 customary lands in the SBB must be regulated in the SBB Regional Regulation Number 13 The year 2019 is no longer the SBB Regional Regulation Number 11 of 2019 which applies because the 92 villages regulated in the SBB Regional Regulation Number 13 of 2019 meet the requirements of a customary land.